Four Chromosome‐Specific (Gossypium barbadense Chromosome 5sh) Upland Cotton RILs with Improved Elongation. Issue 2 (27th April 2017) - Saha, Sukumar; Jenkins, Johnie N.; McCarty, Jack C.; Hayes, R. W.; Stelly, David M.; Campbell, B.T.
Abstract : A chromosome‐specific recombinant inbred line (CS‐B05shRIL) population was created from a cross of TM‐1, the genetic standard line of Gossypium hirsutum L., and CS‐B05sh, a previously released interspecific chromosome substitution line in which all of the chromosome pairs are genetically similar to those of TM‐1, except for the short arm of chromosome 5, which is substituted from 3‐79 ( G. barbadense L.). Four of the fifty CS‐B05shRILs were selected and released on the basis of their improved elongation ranging from 7.37 to 7.84%. The four selected RILs are identified as CS‐B05shRIL‐93 (Reg. No. GP‐1014, PI 677339), CS‐B05shRIL‐68 (Reg. No. GP‐1013, PI 677337), CS‐B05shRIL‐66 (Reg. No. GP‐1012, PI 677336), and CS‐B05shRIL‐10 (Reg. No. GP‐1011, PI 677334).The fiber properties among the CS‐B05ShRILs were compared with those of commercial cultivars DP 393 and PHY 370 WR, which had elongations of 6.86 and 6.25%. Commercial lines performed better for agronomic traits than the released lines. Fiber elongation (the ability to stretch before breaking) is a critical trait in determining yarn quality. The combination of strength and elongation in a fiber determines the energy needed to break either a fiber or a yarn. Due to changes in textile technologies, the global market demands cotton cultivars with improved potential for tensile properties. These germplasm lines are released to incorporate improved elongation genes from only the short arm of chromosome 5 of G. barbadense, thereby reducing genetic drag effect compared with the conventional method of interspecific introgression involving the whole genome.